2008
DOI: 10.1111/j.1463-6409.2008.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel implications for the basal internal relationships of Gastrotricha revealed by an analysis of morphological characters

Abstract: Novel implications for the basal internal relationships of Gastrotricha revealed by an analysis of morphological characters. -Zoologica Scripta , 37 , 429-460. A cladistic analysis of Gastrotricha based on morphological characters is presented. Unlike previous morphological analyses, our study uses species rather than higher level taxa, for which the ground pattern is often unknown. The analysis comprises 79 ingroup taxa, 4 outgroup taxa and 135 binary and multistate characters in total. Character coding is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
87
0
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(108 citation statements)
references
References 65 publications
(178 reference statements)
10
87
0
11
Order By: Relevance
“…Travis 1983;Ruppert 1991;Hochberg and Litvaitis 2000;Ax 2001). Kieneke et al (2008) concluded from a re-evaluation of morphological data that the genus Neodasys represents the sister taxon of all other gastrotrichs (Fig. 11e, f).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Travis 1983;Ruppert 1991;Hochberg and Litvaitis 2000;Ax 2001). Kieneke et al (2008) concluded from a re-evaluation of morphological data that the genus Neodasys represents the sister taxon of all other gastrotrichs (Fig. 11e, f).…”
Section: Discussionmentioning
confidence: 99%
“…If the superordinate structure is not present, all following substructures have to be coded as inapplicable states (-). Most character states are linked to a certain taxon (species) to simplify comparability (Kieneke et al 2008 called this ''morphological type concept'').…”
Section: Phylogenetic Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…O táxon, com distribuição cosmopolita, é composto por mais de 760 espécies tradicionalmente dividido em duas grandes ordens: Chaetonotida e Macrodasyida (Hochberg & Litvaitis, 2000;Balsamo et al, 2008;2009;Todaro & Hummon, 2008;Hummon & Todaro 2010; mas veja Kieneke et al, 2008). O grupo Chaetonotida apresenta mais de 450 espécies, ou seja, compreende a maioria dos Gastrotricha, e possui representantes com uma morfologia externa que lembra o formato de um "pino de boliche".…”
unclassified